Nutritional Quality and Consumer Acceptability of Cookies Enriched with Taro, Moringa Leaf, and Mung Bean Flour - Ety Yuni Ristanti; Muhamad Asrar (Poltekkes Kemenkes Palu, 2025)
Introduction: Taro, moringa leaf, and mung bean are local food ingredients known for their high nutritional content and dietary fiber as alternative substitutes for wheat flour in cookie production. This study evaluated the nutrient quality and consumers acceptability of cookies enriched with taro flour, moringa leaf flour and mung bean flour. Methods : The study was an experimental design using a Completely Randomized Design (CRD), consisting of three treatments with three repetitions. The cookies formulations varied the proportions of wheat flour, taro flour, moringa leaf flour, and mung bean flour as follows: P1 (60%:10%:1%:29%), P2 (50%:20%:2%:28%), and P3 (40%:30%:3%:27%). Data for protein, fat, carbohydrate content, dietary fiber were analyzed using one-way ANOVA, while consumer acceptability was assessed using the Friedman test. Results : Statistical analysis revealed significant differences (P < 0.05) in the protein, carbohydrate and dietary fiber contents among the formulations. Cookies formula F2 had the highest nutrient content. Consumer acceptability ratings ranged from moderate to extreme liking for all cookies variants. Conclusion: Substituting wheat flour with taro flour, moringa leaf flour and mung bean flour resulted in nutrient-dense cookies and well-accepted by consumers. These cookies can be considered a practical, nutrient-dense, and high-fiber snack alternative